Principal Component Analysis (PCA) of Body Measurements and Its Relationship with Body Weight in Jowo Super (Bangkok × Layer) Chicken - Tamsil, Mohammad Hasil; Bayu Putra, Widya Pintaka (Jurnal Veteriner; Vol 25 No 2 (2024)DO - 10.19087/jveteriner.2024.25.2.225, 2024)
The aim of this study was aimed to determine the total variation of the body weight (g) by using principal components analyses (PCA) of body measurements (cm) in 156 Joper (Bangkok × Layer) crossbred chickens consisting of 60 males and 96 females. In total twelve traits including body weight (BW), head circumference (HC), neck length (NL), wings length (WL), back length (BL), chest circumference (CC), chest width (CW), femur length (FL), tibia length (TiL), shank length (SL), shank circumference (SC) and third toe length (TL) were measured in each bird. The PCA of body measurements was performed by using a SPSS 16.0 package. Results determined three PC’s in each sex group based on the body measurements. Five body measurements of WL, BL, FL, TiL and SL were included in the first component (PC1) in both sex group which were able to explain the BW variation by 76% in male and 61% in female. The first three PC explained 67.78% and 65.93% of total variance of the morphostructure of male and female birds, respectively. The Kaiser-MeyerOlkin (KMO) value in both sex group was 0.80 which indicated the results of PC analyse were accurate. In conclusion, the body measurements of PC1 were influenced to BW of birds study.